2001
DOI: 10.1159/000052681
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Aphasia: Whose Perspectives?

Abstract: This paper reviews some different meanings of the term ‘psychosocial’ and identifies the different ways in which the social and psychological sequelae of aphasia can be explored. These include qualitative methods, which seem well suited to addressing such complex issues. Having outlined some features of qualitative research, the paper describes a study in which fifty people talked about the consequences and significance of their long-term aphasia. Their ‘insider perspective’ on aphasia suggests its impacts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 25 publications
6
75
0
7
Order By: Relevance
“…14,66,67 Patients have also been reported to experience uncertainty about the expected trajectory of recovery and possible implications. 46,63,68 Similar findings have been reported in relation to aphasia 69 and eating disabilities following stroke. 43,70 Other studies have focused on the specific problems of loss of ability to drive, 71 and the problems of returning to the work force, particularly for younger people.…”
Section: Life After the Acute Eventsupporting
confidence: 81%
“…14,66,67 Patients have also been reported to experience uncertainty about the expected trajectory of recovery and possible implications. 46,63,68 Similar findings have been reported in relation to aphasia 69 and eating disabilities following stroke. 43,70 Other studies have focused on the specific problems of loss of ability to drive, 71 and the problems of returning to the work force, particularly for younger people.…”
Section: Life After the Acute Eventsupporting
confidence: 81%
“…Investigations using qualitative designs have been regarded as having insufficient precision, objectivity, and rigour. However, qualitative research designs are attracting interest within aphasiology and may prove to be better suited to capture the complexity of communication processes and the contexts in which they occur (Damico & SimmonsMackie, 2003;Kearns, 1999;Lyon, 1999;Parr, 2001). This paper has suggested that the qualitative case study design is a viable research tool to study the psychosocial consequences of aphasia.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Leisure and recreation activities are often described as the most disturbed activities after stroke and aphasia (Dalemans et al, 2008;Hinckley, 2002;Le Dorze & Brassard, 1995;Parr, 2001), both in terms of affected social activities and contacts, as well as interactions and social relationships. All participants reported restricted activities, which have important implications for stroke and aphasia long-term recovery given the role of social engagement in healthy living and wellbeing (Cruice et al, 2003).…”
Section: Activities Limitations / Participation Restrictionsmentioning
confidence: 99%